1971
DOI: 10.2134/agronj1971.00021962006300060001x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seedbed Configuration and Cotton Bur Mulch on Lint Cotton Yield, Soil Water, and Water Use1

Abstract: Better management techniques and planting schemes are needed for the dryland agriculture of the Southern High Plains of the U.S. To test various possibilities cotton (Gossypium hirsutum L.) was grown on three seedbed configurations (flat, ridge, and furrow) with four mulch rates (0.0, 5.6, 11.2, and 22.4 tons/ha of cotton bur mulch). Soil water was measured to a depth of 300 cm by the neutron method. Preseason soil water storage (mid‐January to mid‐June) was highest for the 22.4 tons/ha mulch and least for no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…There are several reports of higher yield from the ridge system (Carter et al, 1965;Atakisi and Gencer, 1977;Boquet et al, 1994). However, Koshi and Fryreap (1971) and Yesilsoy et al (1989) found no difference between ridge and conventional systems in terms of cotton yield.…”
Section: Introductionmentioning
confidence: 94%
“…There are several reports of higher yield from the ridge system (Carter et al, 1965;Atakisi and Gencer, 1977;Boquet et al, 1994). However, Koshi and Fryreap (1971) and Yesilsoy et al (1989) found no difference between ridge and conventional systems in terms of cotton yield.…”
Section: Introductionmentioning
confidence: 94%